Impact of new healthcare legislation and price policy on healthcare services provider at the time of financial crisis. A 10 years study - Malovecka, Ivona; Papargyris, Konstantinos; Minarikova, Daniela; Foltan, Viliam; Jankovska, Anezka (Farmeconomia. Health economics and therapeutic pathways, 2015)
Monitoring, calculation and assessment of healthcare services prosperity in the community pharmacy with the help of financial analysis indicators for the years 2003-2012, using financial statements was conducted, with respect to profitability, debt, liquidity, working capital, and efficiency parameters. These ratios reflect various changes that hold between years 2003 and 2012. Under the time of financial crisis, recession and serious socio-economic changes the profitability parameter Gross Profit ranged from 2003-2011 = 16.12-22.79% (average = 19.20%; mean = 19.78%; σ = 2.41), but in 2012 decreased on 14.35%. Net Profit ranged 2003-2011 = 10.96-18.3% (average = 14.62%; mean = 16.62%; σ = 4.92), while in 2012 reached only 2.29%. Debt ratio ranged from 2003-2012= 2.33-4.81 (average = 3.44; mean = 3.07; σ = 0.82). Liquidity parameters Current Ratio spread between 2003-2012 = 1.13-1.71 (average = 1.43; mean = 1.46; σ = 0.15) and Quick Ratio spread between 2003-2012 = 0.72-1.27 (average = 1.07; mean = 1.09; σ = 0.15). Working Capital Ratio ranged from 2003-2012 = 2.66-12.94 (average = 9.58; mean = 10.06; σ = 3.1) and efficiency ratios were measured either. All changes that have taken place in the society had an impact on community pharmacy finance by worsening its profitability, liquidity, working capital and some of efficiency parameters. Therefore the stability of community pharmacy may be threatened and may affect its future performance.